1989
DOI: 10.1002/bit.260340906
|View full text |Cite
|
Sign up to set email alerts
|

Acetone–butanol–ethanol (ABE) production in a novel hollow fiber fermentor–extractor

Abstract: Acetone-butanol-ethanol (ABE) production by immobilized C. acetobutylicum cells is studied in a novel microporous hollow fiber based tubular fermentor-extractor. The solvent 2-ethyl-l-hexanol is used for in situ dispersion-free extraction of products. A mathematical model for simultaneous fermentation and extraction of the products has been investigated. The predicted as well as experimental data follow the same trend. The experimentally observed value of total solvent productivity increased by more than 40% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Both predicted and experimental data follow the same trend. The experimentally observed value of total solvent productivity increased by >40% as a result of in situ solvent extraction [156]. Unfortunately, good extractants for BuOH, such as decanol, are toxic to C. acetobutylicum.…”
Section: In Situ Extractive Fermentationmentioning
confidence: 95%
“…Both predicted and experimental data follow the same trend. The experimentally observed value of total solvent productivity increased by >40% as a result of in situ solvent extraction [156]. Unfortunately, good extractants for BuOH, such as decanol, are toxic to C. acetobutylicum.…”
Section: In Situ Extractive Fermentationmentioning
confidence: 95%
“…Volesky and Votruba 11 developed mathematical models for a fermentor operating in different modes, and more recently, Shi et al 12 evaluated the performance of a continuous flash extractive process in terms of productivity, energy requirement and product purity. Other examples can be found in Honda et al 13 and Shukla et al 14 Our previous study 15 was the only work found in the literature concerning the use of mathematical optimisers in the ABE fermentation. For this reason, it is necessary to evaluate the performance of mathematical optimisation techniques for the ABE processes, which can be a very useful tool in the search for economic feasibility of biobutanol plants by operating them in optimised conditions.…”
Section: Introductionmentioning
confidence: 93%
“…Thus the flash fermentation process was simulated by solving two deterministic models, one that represents the fermentor and the other the flash tank. The equations that represent the dynamics of the fermentor (Equations (1) to (3)) in conjunction with the mass balances of the flow streams (Equations (12) and (13)) and the flash calculation (Equations (14) and (15)) were solved using a Fortran program. Integration of Equations (1) to (3) was carried out using a fourth-order Runge-Kutta method.…”
Section: Process Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, only ultrafiltration (UF) or microfiltration (MF)-based processes have been reported and little is known on the application of reverse osmosis (RO) or nanofiltration (NF) in membrane bioreactors. Additionally, membrane contactor systems have been developed, based on microporous polyolefin or teflon membranes [52][53][54][55].…”
Section: Membrane Bioreactorsmentioning
confidence: 99%